REGION SPECIFIC WAVELET COMPRESSION FOR 4K SURVEILLANCE IMAGES - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
For successful transmission of massively sequenced images during 4K surveillance operations large amount of data transfer cost high bandwidth, latency and delay of information transfer. Thus, there lies a need for real-time compression of this image sequences. In this study we present a region specific approach for wavelet based image compression to enable management of huge chunks of information flow by transforming Harr wavelets in hierarchical order. Â Â